Felony Disenfranchisement: Factors Relating to Support for Restoration - Karpf, Alexis K (2020)
Felony Disenfranchisement, a collateral consequence, strips justice-involved individuals of their voting rights. While this policy is enacted in 48 states and the District of Columbia, a majority of community members are unaware of its existence. The current study used three hypotheses to guide its research about how education about disenfranchisement policy impacts a community member's opinion:1) Participants exposed to information about the effects of disenfranchisement will be more supportive of enfranchisement than those in the control condition; 2) Participants who receive the vignette featuring the White justice-involved individual will indicate a higher level of support for enfranchisement compared to those who received the vignette about the Black justice-involved individual; 3) Participants that showed high support for felony enfranchisement will show a similarly high level of support for educational access, employment assistance, and housing aid. The data of 346 community members were analyzed and implications of the results are discussed within this paper